Original paperPulsed-dose-rate post-operative vaginal cuff brachytherapy for endometrial cancer: preliminary report - Serkies, Krystyna; Pawłowska, Ewa; Kaminska, Joanna; Lipniewicz, Joanna; Narkowicz, Magdalena; Jassem, Jacek (Journal of Contemporary Brachytherapy, 2015)
Purpose: To present our early experience with the post-operative intracavitary pulsed-dose-rate vaginal brachytherapy (PDR VBT) in high-intermediate risk endometrial cancer patients as defined in the PORTEC-2 trial. Material and methods : The study group included 60 high-intermediate risk endometrial cancer patients with a median age of 64 (range: 57-87) treated between April 2010 and December 2013 with PDR VBT at a dose of 18 Gy (range: 17-27); 1 Gy/pulse, pulses repeated every hour. Prior surgery consisted of a total abdominal hysterectomy and bilateral salpingo-oophorectomy with or without a lymphadenectomy. Results: After a median follow-up of 23 months there were two local recurrences, both located in the lower part of the vagina, outside of the irradiated area. One of the relapsed women was susccessfully salvaged with surgery followed by pelvic irradiation and remained free of the disease for the subsequent three years. Following therapy, 24 (40%) of the patients experienced grade 1 or 2 urinary and/or bowel toxicity. There was one case with a serious post-surgical (grade 3) urinal side effect. Conclusions : Post-operative PDR VBT at a dose of 18 Gy/18 pulses/every hour seems to be a safe technique and ensures vaginal control in high-intermediate risk endometrial cancer patients. Additional follow-up including larger number of patients is necessary for the final assessment of this therapy.